Acromegaly in Primary Empty Sella (Journal of Medicine, 2009)
Acromegaly has occasionally been found in patients with an empty sella secondary to prior pituitary irradiation and/or surgery. Active acromegaly, on the other hand, has only rarely been found in patients with a primary empty sella. The two most commonly held hypotheses concern-ing the aetiology of the primary empty sella are hydrodynamic transmission of cerebrospinal fluid pressure through a congenital defect in the diaphragm sella, and infarc-tion of the pituitary contents. Pituitary masses may undergo clinically silent infarction with development of a partial or totally empty sella by cerebrospinal fluid filling the dural herniation. Here we describe a patient who has empty sella without any prior pituitary procedures. Keywords: Acromegaly, empty sella syndrome, growth hormone.   doi: 10.3329/jom.v10i2.2827   J MEDICINE 2009; 10 : 119-120